Study of alternative oxidase as possible molecular marker for phylogenetic analysis of the Botrytis cinerea - Szojka, Anikó; Sándor, Erzsébet (Acta Agraria Debreceniensis, 2014)
Botrytis cinerea (teleomorph Botryotinia fuckeliana (de Bary) Whetzel) is able to attack several economically important plants causing gray rot. Botrytis cinerea species complex includes two cryptic species (B. cinerea and B. pseudocinerea) that tolerate fungicides differently. On the basis of classical taxonomic markers, the two related species are very difficult to be distinguished; therefore, their separation is usually performed using molecular methods based on the time-consuming molecular analysis of several markers. Our goal was to find markers, which are suitable for the differentiation. Testing the nucleotide sequences of the alternative oxidase encoding gene, B. cinerea and B. pseudocinerea strains were clearly differentiated. Moreover, the analysis of the protein sequences of the enzyme with the maximum likelihood method reflected well the taxonomic relationships of the different fungi.